A clinical efficacy analysis of ankle arthrography-assisted modified ankle capsule repair in the treatment of recurrent bunion cysts - Fu, Yongbin; Mei, Siwei; Ma, Mingming; Ruan, Xiaojun; Ning, Tao (Frontiers in Surgery, 2025)
ObjectiveThis study aims to retrospectively analyze the clinical efficacy of ankle arthrography-assisted modified ankle capsular repair for treating recurrent bunion cysts.MethodsClinical data from 16 cases of recurrent bunion cysts, treated between December 2021 and June 2024, were collected. All patients underwent intraoperative ankle arthrography with cyst excision, followed by ankle capsule repair based on the arthrography results. Patient gender, age, the presence of ankle arthrography during interstitial traffic with the cyst, and any postoperative complications were documented. Clinical outcomes were monitored during the postoperative follow-up.ResultsIn 14 out of 16 patients, ankle arthrography revealed communication of the contrast medium with the bunion cyst through the tendon sheath of the Flexor hallucis longus (FHL) tendon. In the remaining two patients, no contrast medium spillage was observed. The surgical incisions healed without infection, and a follow-up period of 3–24 months revealed only one recurrence.ConclusionAnkle arthrography-assisted modified ankle capsule repair is an effective method to reduce recurrence rates in patients with recurrent bunion cysts, particularly those communicating with the ankle joint via the FHL tendon sheath.